Development of an AI-Based Eco Digital Storytelling Model to Develop the Ecological Intelligence of Elementary School Students: Pengembangan Model Eco Digital Storytelling Berbasis AI Untuk Mengembangkan Kecerdasan Ekologis Siswa Sekolah Dasar - Feby Kharisna; Yulia Darniyanti; Dhara Atika Putri; M. Anggrayni (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2026)
The low level of students' ecological intelligence and the limited integration of digital technology into environmental learning require innovative instructional models that are responsive to technological advances. This study aimed to develop an Eco Digital Storytelling Model Based on Generative Artificial Intelligence (AI) to enhance elementary school students' ecological intelligence. The study employed a Research and Development (R&D) approach using the ADDIE development model, consisting of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research was conducted with fifth-grade students at SD Negeri 15 Koto Baru and SD Negeri 09 Sitiung, Dharmasraya Regency, Indonesia. Data were collected through observations, interviews, expert validation, practicality questionnaires, learning implementation observations, and pretest-posttest assessments. Data were analyzed using descriptive and inferential statistics, including validity analysis, practicality analysis, N-Gain analysis, and paired sample t-test. The findings revealed that the developed model consists of six learning stages: Eco Explore, Story Planning, AI Story Creation, Deep Reflection, Eco Action, and Sharing & Evaluation. The model met the criteria of validity, practicality, and effectiveness for implementation in elementary education. Its implementation enhanced students' engagement, critical thinking, creativity, and digital literacy while improving ecological knowledge, awareness, attitudes, decision-making skills, and pro-environmental actions. The novelty of this study lies in integrating Education for Sustainable Development (ESD), Digital Storytelling, Generative Artificial Intelligence (AI), and the Deep Learning approach into a comprehensive instructional model, providing an innovative framework for environmental education that addresses the demands of twenty-first-century learning and supports sustainable education in elementary schools.